Hibah yang Ditarik Kembali Perspektif Hukum Islam dan KuhPerdata - Febrianti B; Musyfika Ilyas (Shautuna: Jurnal Ilmiah Mahasiswa Perbandingan Mazhab dan Hukum, 2021)
This study discusses the withdrawn grant from the perspective of Islamic law and the Civil Code (a case study in Somba Opu sub-district, Gowa district). The type of research used by the author in this study is a type of qualitative research using two data sources, namely primary data and secondary data. In the method of data collection, researchers conducted observations, interviews and documentation. The research implementation procedure is the identification stage and the data processing stage. Analysis of the data used with data reduction steps, data presentation, and data verification. The results of this study indicate that there are two views from the Islamic legal point of view regarding withdrawn grants. the withdrawal of grants that have been given provided that one of the categories mentioned in the discussion chapter is fulfilled